Awake prone positioning in COVID-19 pneumonia in India: A useful strategy in resource limited setting - Raja Dhar; Shubham Sharma; Praveen Kumar Shahi; Shyam Krishnan; Tarang Kulkarni; Milind Sovani (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2021)
Introduction: Awake prone positioning is being recently used in patients with COVID-19 respiratory failure. While the theory supporting it is strong, the evidence supporting it is lacking. Aim of our study was to assess the effect of awake prone positioning on oxygenation and PaO2/FiO2 in patients with COVID-19 pneumonia. Methods: Retrospective observational cohort data from patients admitted to a tertiary care hospital was collected. Patients deemed suitable for admission to Intensive Care Unit (ICU) but did not need immediate ventilation were included. Patients fulfilling the inclusion criteria were subjected to cyclical prone positioning. pO2, pCO2 and PF ratio was recorded before and after awake prone positioning. Comparative data was analyzed using the SPSS software and student t-test was used for comparison of mean values. Results: Awake Prone positioning was performed in 18 COVID-19 positive patients (16 men, mean age 55). Patients had severe respiratory failure with a mean partial pressure of oxygen (PaO2) of 51.2 mmHg (range 46 to 60) on an arterial blood gas (ABG) sample and a mean PaO2/FiO2 (P/F) ratio of 104. Proning times ranged from one episode of 2 hours to multiple sessions ranging from 30 minutes to a few hours at a time. Prone positioning led to a significant improvement in oxygenation with a mean PaO2 of 61 mmHg (mean change 8.2, 95% CI 7.3 to 12.3 mmHg, p<0.001) and mean PF ratio of 125.9 (mean improving of 21.7, 95% CI 13.6 to 29.7; p<0.001) two hours from start of proning manoeuver. Conclusion: In our cohort, awake prone positing was well tolerated and led to a significant improvement in oxygenation and possibly reduced the need for mechanical ventilation. Whilst we await for definitive studies, its likely that awake proning is going to be used widely, particularly in countries with limited intensive care bed capacity.